Microwave-assisted hydrothermal synthesis of monoclinic bismuth trioxide nanorods: optical and photocatalytic properties - Al-Ghamdi, A. A.; Al-Turki, Yusuf; Aal, Nadia Abdel; Yakuphanoğlu, Fahrettin; El-Tantawy, Farid (Springer, 2017)
Herein, the successful synthesis of bismuth trioxide (Bi2O3) nanorods via a new microwave-assisted hydrothermal technique is reported. Detailed characterizations for the prepared nanorods employing various analytical techniques were considered for their structural, compositional, morphological, optical and photocatalytic properties. The detailed results confirmed that the prepared nanorods have a well-crystalline structure, growing with a high density and having pure monoclinic crystal structure. The prepared nanorods exhibited good optical properties were confirmedly the room-temperature photoluminescence (PL) spectroscopy. The as-prepared Bi2O3 nanorod structures showed efficient photocatalytic activity for the degradation of methyl orange (MO) dyes under the application of UV light irradiation (365 nm). The pseudo-first order reaction rate constant is 0.007 min(- 1). The fabricated Bi2O3 nanorods are very useful as ultraviolet light activated photocatalyst nanorod materials for decomposing methyl orange and various types of organic dyes.
Keywords: Morphological Control; Degradation; Bi2O3; Dye; Nanoparticles